Analisis Yuridis Putusan Pengadilan Nomor 251/Pid.Sus/2015/PN.Sda tentang Kasus Kecelakaan yang Mengakibatkan Matinya Orang di Pengadilan Sidoarjo - Wulayana, Damar; Rosnawati, Emy (ResearchJet Journal of Analysis and Inventions, 2024)
This study aims to determine whether the court’s decision number 251/Pid.Sus/2015/PN.Sda is a traffic accident that occurs due to negligence of the vehicle driver. Factors that cause traffic accidents come from drivers who are sleepy and less careful. Driver negligence which results in the death of people in traffic accidents is regulated in article 359 of the criminal code and can also be given sanctions or fines as regulated in Article 310 of Law No 22 of 2009. Therefore, the author uses the method Normative juridical as a from of implementation. The formulation of the promblem studied is to analyze the juridical court decision Number 251/Pid.Sus/2015/PN.Sda regarding negligence which resulted in the death of a person, finally legally resulted in the defendant being sentenced to 1 year in prison.